[INVITED] Epsilon-near-zero metalenses operating in the visible: Invited paper for the section : Hot topics in Metamaterials and Structures. (June 2016) - Pacheco-Peña, V.; Navarro-Cía, M.; Beruete, M.
Abstract: Several converging lenses working in the permittivity near to zero (ENZ) regime at optical frequencies are designed using an array of metal-dielectric-metal plasmonic waveguides. These plasmonic waveguides show a dispersive nature that enable to mimic an effective ENZ medium when using the fast wave transverse electric (TE1 ) mode near its cut-off wavelength. By arranging multiple plasmonic waveguides with the correct engineered dimensions, several metalenses, including graded index (GRIN) ones, and diffractive optical elements (i.e., zoned metalenses) are proposed. The metalenses are designed at λ 0 =474.9 nm ( f =631.67 THz) with a focal length of 10.75 λ 0 . Numerical results demonstrate that the best performance is obtained for the case of the GRIN metalens in terms of the focal position, transversal resolution and thickness, reducing its volume up to ∼52.3% with respect to the smooth-profiled plano-concave metalens. Highlights: A metal-dielectric-metal plasmonic waveguide is used to synthesize an ENZ medium. The ENZ performance of the waveguide is evaluated analytically and numerically. The ENZ plasmonic waveguide is used in the design of several metalenses. Graded index ENZ metalens shows the best overall performance.